2013
DOI: 10.1021/ja410052u
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Defined Silica-Supported Tungsten Oxo Alkylidene Is a Highly Active Alkene Metathesis Catalyst

Abstract: Grafting (ArO)2W(═O)(═CHtBu) (ArO = 2,6-mesitylphenoxide) on partially dehydroxylated silica forms mostly [(≡SiO)W(═O)(═CHtBu)(OAr)] along with minor amounts of [(≡SiO)W(═O)(CH2tBu)(OAr)2] (20%), both fully characterized by elemental analysis and IR and NMR spectroscopies. The well-defined oxo alkylidene surface complex [(≡SiO)W(═O)(═CHtBu)OAr] is among the most active heterogeneous metathesis catalysts reported to date in the self-metathesis of cis-4-nonene and ethyl oleate, in sharp contrast to the classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 14 publications
4
81
0
2
Order By: Relevance
“…In contrast, using Surface Organometallic Chemistry, [3][4][5][6] a large family of highly active supported alkene metathesis catalysts has been reported based on welldefined metal alkylidenes in the past 15 years. [7][8][9][10][11][12][13][14][15] These numerous complexes have given access to a large number of spectroscopic and catalytic data set that have contributed to a better understanding of the mechanism and reaction intermediates involved in alkene metathesis. 10,12,14 In an attempt to bridge the gap between these and classical illdefined WO 3 /SiO 2 catalysts, 1,2,16 we have recently investigated the synthesis of silica supported oxo alkylidene complexes, which present very high activity ( Figure 1b).…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…In contrast, using Surface Organometallic Chemistry, [3][4][5][6] a large family of highly active supported alkene metathesis catalysts has been reported based on welldefined metal alkylidenes in the past 15 years. [7][8][9][10][11][12][13][14][15] These numerous complexes have given access to a large number of spectroscopic and catalytic data set that have contributed to a better understanding of the mechanism and reaction intermediates involved in alkene metathesis. 10,12,14 In an attempt to bridge the gap between these and classical illdefined WO 3 /SiO 2 catalysts, 1,2,16 we have recently investigated the synthesis of silica supported oxo alkylidene complexes, which present very high activity ( Figure 1b).…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…4,5 Major research efforts have been conducted in the past 40 years to generate the corresponding well-defined molecular and surface mimics (Figure 1C). 4,610 Such catalysts display very high activity at room temperature (> 100 turnover number (TON)/min) 11,12 in contrast to industrial catalysts, showing that the low activity of the industrial WO 3 /SiO 2 catalysts is presumably due to the difficulty to generate the active oxo alkylidene from the oxo surface species rather than an intrinsic low activity of tungsten oxo alkylidene moieties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that well-defined zirconium hydrides supported on alumina are highly active catalysts for alkane hydrogenolysis (Fig. 6a) [74] and silica-supported tungsten [75][76][77][78] and molybdenum complexes (Fig. 6b) [79][80][81][82] are effective catalysts for alkane metathesis [69,71,77,[83][84][85].…”
Section: Introductionmentioning
confidence: 99%